Assessing Cerebrovascular Hemodynamics Using Transcranial Doppler in Patients with Mechanical Circulatory Support Devices. Issue 3 (10th February 2020) - Melmed, Kara R.; Schlick, Konrad H.; Rinsky, Brenda; Dumitrascu, Oana M.; Volod, Oksana; Nezhad, Mani; Padrick, Matthew M.; Runyan, Carmelita; Arabia, Francisco A.; Moriguchi, Jaime D.; Lyden, Patrick D.; Song, Shlee S
ABSTRACT: BACKGROUND AND PURPOSE: Mechanical circulatory support (MCS) devices are commonly used in heart failure patients. These devices carry risk for presumably embolic and additionally hemorrhagic stroke. Alterations in blood flow play a key role in stroke pathophysiology, and we aimed to learn more about hemodynamic compromise. In this study, we used transcranial Doppler (TCD) ultrasound to define hemodynamics of commonly used nonpulsatile MCS devices, as well as pulsatile devices, with special attention to the total artificial heart (TAH). METHODS: From 2/2013 through 12/2016, we prospectively enrolled patients with MCS who underwent TCD imaging. We analyzed TCD parameters, including peak systolic velocity, end‐diastolic velocity, pulsatility indices (PIs), and number of high‐intensity transient signals. Waveform morphologies were compared between various MCS devices. RESULTS: We performed 132 TCD studies in 86 MCS patients. Waveforms in patients supported by venoarterial‐extracorporeal membrane oxygenation demonstrated continuous flow without clear systolic peaks with an average (±SD) PI of .43 (±.2). PIs were low in patients with continuous‐flow left ventricular assist devices with a mean PI of .32 (±.13). Impella patients had morphologically distinct pulsatile waveforms and a higher mean PI of .65 (±.24). In intra‐arterial balloon pump patients, mean PI was 1.01 (±.16) and diastolic upstrokes were pronounced. In TAH patients, mean middle cerebral artery velocity of 79.69 (±32.33) cm/seconds and PI of .74 (±.14) approached normal values. CONCLUSION: TCD can detect characteristic waveforms in patients supported by various MCS devices. These device‐specific TCD patterns are recognizable and reproducible.